Sistema de Numeração Ixybi(K)O-Á - Karajá Xambioá - KARAJÁ, Welder Wachure Dias Aires (Universidade Federal do Tocantins, 2023)
Passionate about Mathematics I developed an interest in this topic in the year 2021, during the development of a class in the subject of History of Mathematics, in which the subject discussed about the origin of different numbering systems in the world, it reminded me of classes in Inỹ Rubé (our language), still in Elementary and High School when we learn to count numbers in our language. Reflecting on these numbering systems in different peoples and civilizations, although these peoples and civilizations are geographically separated, their numbering systems have several similarities. Moved by this passion and with an interest in investigating the numbering system of my people, the Karajá Ixybi(k)o-á (a friend of the people), who enter the community and family contexts of elders, chiefs, teachers and the intellectuals of the Karajá Ixybi(k)o-á culture, so that with them we can describe this numbering system to many hands and feet. From this perspective, the question that prompted this work was: In what terms do the Karajá Ixybi(k)o-á indigenous people mobilize the practices of the numbering system in their daily lives, from their ancestors to the present day? And as objective: To describe the numbering system of the Karajá Ixybi(k)o-á indigenous people, from the perspective of Ethnomathematics. To answer the proposed question and reach the goal, we based ourselves on the narratives of our intellectuals about the Karajá Ixybi(k)o-á numbering system, which revealed to us a broad and complex system that is directly linked to the original knowledge of this people, which involves, among other cosmological elements, the Inỹ rubé language for having specific terms for men and women. It is noteworthy that the structure of this system is through counting that involves the hands and feet. However, it should be noted that even the indigenous people in their relations with non-indigenous people, where they use the Indo-Arabic numbering system, but among the oldest in the villages, the Ixybi(k)o-á system meets their daily needs.